PENGARUH AUGMENTED REALITY BERBASIS WEB DENGAN MODEL PROBLEM BASED LEARNING TERHADAP SIKAP PEDULI LINGKUNGAN PESERTA DIDIK - Dwi Ratnasari; Mahrawi Mahrawi; Indria Wahyuni; Licia Octaviana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This investigation aims to investigate the impact of combining a Problem-Based Learning framework with Web-based Augmented Reality media on students' environmental concern attitudes when learning about biologically related biodiversity. This research is a quasi-experimental study that utilizes a research design consisting of a control group that is only posttest based. The classes X MIPA 1 and 3 served as the experimental class, while X MIPA 2 and 4 served as the control class. The research population was students enrolled in class X SMAN 4 in Serang City during the academic year 2021/2022. The samples consisted of all four classes. The sampling was done using a method known as random sampling. The instrument employed is a questionnaire about environmental care attitudes. Data collecting strategies used interview sheets, questionnaires, observation sheets, and documentation. The study's results that used an Independent sample t-Test to test the effect of using Web-based Augmented Reality media with a Problem Based Learning model on people's attitudes toward caring for the environment showed that a score of 0.002 was obtained. These findings were based on the study that used the test. According to the research findings, one may conclude that there is an influence of employing Web-based Augmented Reality media in conjunction with a Problem Based Learning paradigm on the students of SMAN 4 in Serang City's attitude toward caring for the environment.